Comparing A-Mode Biometry, B-Mode Biometry and IOL Master in Measurement of Axial Length : Phaco - Amoozadeh , Maedeh; Ghorbanalizadeh, Farzaneh; Noorizadeh, Farsad; Shojaei, Ahmad; Sobhani, Soheila; Vafaei, Ali; Moradi, Ali (Journal of Ophthalmic and Optometric Sciences, 2019)
Background: To perform a comparison of axial length (AL) measurements using A-mode biometry, B-mode biometry and IOL Master. Material and Methods: Axial length among patients undergoing cataract surgery in Basir Eye Clinic, Tehran, Iran from May 2017 and September 2017 was determined pre-operatively using three methods. Axial length was first measured using IOLMaster 500 (Carl Zeiss Meditec, Jena, Germany), then by A-mode biometry using immersion technique and finally using horizontal axial B-scan immersion biometry. The interval between each examination was 5 minutes. Results: Statistical analysis revealed strong correlations between AL measurement values obtained from A-mode and B-mode (r = 0.983, p < 0.001), A mode and IOLMaster (r = 0.999, p < 0.001) as well as B-mode and IOLMaster (r = 0.984, p <0.001). All correlations were strong but the strongest correlation was observed between A mode and IOLMaster methods. Conclusion: A-mode biometry showed a stronger correlation with IOL Master AL readings compared to B-Mode, thus when there are limited resources and the optical method is not accessible, A-mode immersion echography is proffered as an alternative to IOLMaster. Keywords: Biometry; IOLMaster; Axial Length; Comparison.